Persepsi Konsumen terhadap Kualitas Pelayanan di My Beauty Spa Jambi - Pupu Sopini (J-MAS (Jurnal Manajemen dan Sains), 2018)
This research aims to know the consumer's perception of the quality of service at My Beauty Spa Jambi. A good quality of service will improve the quality of a company in the eyes of consumers. When the quality provided is in compliance with the wishes and expectations of consumers then this will increase the level of consumer satisfaction toward services. The methods used are ex post facto research. that is examining the events that have happened and then meruntut into the back to find out the factors that can lead to the onset of an event. The results showed consumers ' perception of the quality of service at My Baeuty Spa overall are on a very good category with an average score of 430.2, meaning that the dimension of responsiveness, assurance and empathy are each giving a score an average of 441, 455.25 and 475, with 72 categories very well. While the dimensions of the intangibles and the reliability of each of the stated score average is 380 and 399 respondents said criteria, that is good for the dimension. These dimensions will affect on the level of customer satisfaction in My Beauty Spa, the more satisfied consumers in the given service it will increase the number of customers. Keywords: Consumer perceptions of service quality,